1996
DOI: 10.1017/s0022215100132955
|View full text |Cite
|
Sign up to set email alerts
|

Septoplasty as a day-case procedure – a two centre study

Abstract: Day-stay surgery is an integral part of Otolaryngology. Many procedures which have traditionally been thought to require overnight stay can be carried out on a day care basis. We report our experience of treating 163 patients admitted for septal surgery as a day-case procedure. The paper summarizes the experience of two centres. One of these is a London Teaching Hospital, where surgery was performed through a dedicated day-case unit, and the other is a District General Hospital where patients were admitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 6 publications
2
21
0
1
Order By: Relevance
“…These readmission rates are lower than those reported in the contemporary literature [4,8,11]. The readmission rate for (septo)rhinoplasty is 1.38% and the overstay rate is 9.22%.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…These readmission rates are lower than those reported in the contemporary literature [4,8,11]. The readmission rate for (septo)rhinoplasty is 1.38% and the overstay rate is 9.22%.…”
Section: Discussionmentioning
confidence: 64%
“…However, previous reports have advocated day case septal surgery as a safe and effective practice [4-6]. Furthermore, a subjective patient based study showed that septoplasty is generally acceptable to the patient in terms of pain and overall satisfaction parameters [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies and guidelines issued by medical organizations have subscribed to an unexpected postoperative admission rate of 0.5% [6], 1.8% [7], 2-3% [11], 4% [9]. In the period of 3 years there were no cases that required post-operative admission for treatment or observation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are more studies available than for antrostomy. Several older studies drew conflicting conclusions regarding day-case management of septoplasty, due to readmission rates that varied from 2% to 13.4% [27][28][29][30][31].…”
Section: Guideline 14mentioning
confidence: 99%